(untitled) (Journal of actual problems of jurisprudence, 2019)
In our opinion, the proposed changes and additions to the existing Code of Administrative Offences will find their application and securing a future version of the rules of the Administrative Procedure Code of Kazakhstan, as well as norms of CPC and the CPC